2013
DOI: 10.5539/ijef.v5n5p171
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of the Global Financial Crisis to the East Asian Equity Markets

Abstract: This paper investigates the transmission mechanism of the Global Financial Crisis originated in the United States to the East Asian equity markets, including the developed markets (Hong Kong, Japan and Singapore), emerging markets (Malaysia, Thailand and Taiwan) and frontier market (Vietnam). To test for the transmission, we employ the constant conditional correlation (CCC) and the dynamic conditional correlation (DCC) based on the MGARCH model to estimate the time-varying correlations between the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although there is a little doubt about the advantages of international economic integration, a few recent years have shown in practice the other side of the coin. In 2007 the crisis, which initially affected the financial system of the United States, shortly spread all over the world and stimulated the economic recession, with both business and ordinary citizens suffering from its consequences (Thao et al 2013;Kowalski 2012). In many countries the financial crisis caused a rapid decrease in tax revenues, while austerity measures in fiscal policy (raising taxes and cutting public spending) applied by governments even deepened the economic problems (Adam, Iacob 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a little doubt about the advantages of international economic integration, a few recent years have shown in practice the other side of the coin. In 2007 the crisis, which initially affected the financial system of the United States, shortly spread all over the world and stimulated the economic recession, with both business and ordinary citizens suffering from its consequences (Thao et al 2013;Kowalski 2012). In many countries the financial crisis caused a rapid decrease in tax revenues, while austerity measures in fiscal policy (raising taxes and cutting public spending) applied by governments even deepened the economic problems (Adam, Iacob 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kuper and Lestano (2007) use dynamic conditional correlation to examine the dynamic linkages among financial markets in Thailand and Indonesia. Thao et al (2013) employed the constant conditional correlation (CCC) and the dynamic conditional correlation (DCC). They found that almost all the East Asian markets revealed higher correlations to other markets in the region than the United States, even during the crisis period.…”
mentioning
confidence: 99%